Analyzing the Complexity of Performance Information Use: Experiments with Stakeholders to Disaggregate Dimensions of Performance, Data Sources, and Data Types - Walker, Richard M.; James, Oliver; Lee, M. Jin; Ho, Samuel M. Y. (Public administration review, 2018)
This article addresses important questions about the complex construct of underlying performance information use: public service performance. A between-subjects experimental vignette methodology was implemented to answer questions about the effects of emphasizing different dimensions of performance and the sources and types of performance information among internal and external stakeholders in two service arenas (secondary education and solid waste management) in Hong Kong. The findings indicate common attitudes and agreement across stakeholder groups and services on the merits of archival and external data types. Other results vary by service and between stakeholder groups. The effects of information about effectiveness can depend on its combination with information about efficiency or equity. This complexity needs to be considered when designing information communication to different stakeholder groups.